Extensive Cutaneous T-Cell Lymphoma of the Feet Treated with High-Dose-Rate Brachytherapy and External Beam Radiation - Joy Tao; Courtney Hentz; Michael L. Mysz; Issra Rashed; David Eilers; James Swan; Rebecca Tung; Bahman Emami (Case Reports in Dermatological Medicine)
Cutaneous T-cell lymphoma (CTCL) is a chronic, debilitating disease that has a severe impact on quality of life. We present a patient with multiple CTCL lesions on the bilateral feet, which impaired his ability to ambulate. His lesions on both feet were successfully treated with a total of 8 Gy in two fractions via high-dose-rate surface brachytherapy using the Freiburg Flap applicator. The deeper aspects of the bulkier lesions on the left foot were boosted with electron beam therapy. The radiation therapy was well tolerated, and the patient was able to regain his mobility after completing radiation therapy. To our knowledge, there are few reports utilizing brachytherapy in treating CTCL. Our case describes treatment of larger, more extensive CTCL lesions than previously reported.